Meta-Analysis of Alterations in Regulatory T Cells' Frequency and Suppressive Capacity in Patients with Vitiligo. (16th September 2022) - Giri, Prashant S.; Mistry, Jahanvi; Dwivedi, Mitesh
Abstract : Vitiligo is a noncontagious autoimmune skin depigmenting disease. Regulatory T cells (Tregs) play a key role in maintaining peripheral tolerance; however, Tregs' number, suppressive function, and associated suppressive molecules (FOXP3, IL-10, and TGF- β ) are found to be reduced in vitiligo patients. Although, the role of Tregs in vitiligo pathogenesis is well established, there are several contrary findings which suggest a controversial role of Tregs in vitiligo. Therefore, to clarify the role of Tregs in vitiligo pathogenesis, we aimed to study Tregs' frequency, suppressive capacity, and associated suppressive molecules (FOXP3, IL-10, and TGF- β ) in vitiligo patients through meta-analysis approach. A total of 30 studies involving 1223 vitiligo patients and 1109 controls were included in the study. Pooled results from our meta-analysis suggested significantly reduced Treg cells' frequency in vitiligo patients (p = 0.002 ). Interestingly, Tregs' suppressive capacity was also significantly reduced in vitiligo patients (p = 0.0002 ); specifically, Treg-mediated suppression of CD8 + T cells was impaired in vitiligo patients (p < 0.00001 ). Moreover, FOXP3, a key Tregs' transcription factor, was significantly reduced in blood and skin of vitiligo patients (p < 0.00001 ). Intriguingly, the FOXP3 expression was significantly reduced in the lesional skin as compared to perilesional and nonlesional skin (p = 0.007 and p = 0.04 ). Furthermore, the expression of key Treg-associated suppressive cytokines IL-10 and TGF- β were significantly reduced in vitiligo patients (p = 0.0005 and p = 0.01 ). The disease activity-based analysis suggested for reduced Tregs' frequency and FOXP3 expression in active vitiligo patients (p = 0.05 and p = 0.01 ). We also studied the effect of microRNA-based treatment, narrow band–UVB phototherapy, and Treg-associated treatments on Tregs' frequency, FOXP3, and IL-10 expression. Interestingly, we found increased Tregs' frequency, FOXP3, and IL-10 expression after the treatment (p = 0.007, p < 0.0001, and p = 0.002 ). Overall, our meta-analysis suggests that the Tregs play a crucial role in pathogenesis and progression of vitiligo, and hence, Treg-based therapeutic interventions could be effective in vitiligo patients.